High performance additional mass enhanced film structure triboelectric nanogenerator for scavenging vibration energy in broadband frequency range. (March 2023) - Yu, Hongyong; Xi, Ziyue; Zhang, Yiping; Xu, Ruijiang; Zhao, Cong; Wang, Yawei; Guo, Xinyang; Huang, Yue; Mi, Jianchun; Lin, Yejin; Du, Taili; Xu, Minyi
Abstract: It is highly desired to develop high performance vibration energy scavengers to power amounted and distributed sensors along with the era of Internet of Things. This study proposes a novel additional mass enhanced film structure triboelectric nanogenerator (AMF-TENG) for efficiently scavenging broadband vibration energy. The AMF-TENG is composed of an additional mass, a fluorinated ethylene propylene (FEP) film with a carbon electrode, and a conductive fabric fixed on a hollow frame. The additional mass can enhance the electrical output of the AMF-TENG by 25.5 times due to the vibration amplitude and contact forces between the FEP film and conductive fabric are greatly amplified. The utilization of a hollow frame makes the electrical output of AMF-TENG 150% higher than the enclosed frame. Theoretical analysis and experimental studies were carried out to investigate the design parameters. The experimental results indicate that the AMF-TENG shows good electrical performance in the broadband frequency range from 15 to 70 Hz. Under the vibration condition of 40 Hz and 30 m/s 2, it can generate a maximum power density of 622.59 W/m 3, which is higher than previous studies by 155.2%. Finally, the AMF-TENG is proven to power temperature and humidity sensors continuously under actual machine vibration. In brief, the AMF-TENG provides a new method for efficiently scavenging of vibration energy in the broadband frequency range. Graphical Abstract: This work develops a novel additional mass enhanced film structure triboelectric nanogenerator (AMF-TENG) for efficiently harvesting broadband vibration energy of vehicles, bridges, machines, etc. The AMF-TENG generates the maximum power density of 622.59 W/m 3, which is higher than the best results from previous studies by 155.2%. ga1 Highlights: The additional mass can enhance the electrical output of the AMF-TENG by 25.5 times. The AMF-TENG can efficiently scavenge vibration energy in broadband frequency range. The AMF-TENG can continuously power a temperature and humidity sensor under actual machine vibration. The AMF-TENG can generate a maximum power density of 622.59 W/m 3, which is higher than the previous studies by 155.2%.